Shoulder Surgery in the Beach Chair Position Is Associated with Diminished Cerebral Autoregulation but No Differences in Postoperative Cognition or Brain Injury Biomarker Levels Compared with Supine Positioning: The Anesthesia Patient Safety Foundation Beach Chair Study. (January 2015) - Laflam, Andrew; Joshi, Brijen; Brady, Kenneth; Yenokyan, Gayane; Brown, Charles; Everett, Allen; Selnes, Ola; McFarland, Edward; Hogue, Charles W.
Abstract : BACKGROUND: Although controversial, failing to consider the gravitational effects of head elevation on cerebral perfusion is speculated to increase susceptibility to rare, but devastating, neurologic complications after shoulder surgery in the beach chair position (BCP). We hypothesized that patients in the BCP have diminished cerebral blood flow autoregulation than those who undergo surgery in the lateral decubitus position (LDP). A secondary aim was to examine whether there is a relationship between patient positioning during surgery and postoperative cognition or serum brain injury biomarker levels. METHODS: Patients undergoing shoulder surgery in the BCP ( n = 109) or LDP ( n = 109) had mean arterial blood pressure (MAP) and regional cerebral oxygen saturation (rScO2 ) monitored with near-infrared spectroscopy. A continuous, moving Pearson correlation coefficient was calculated between MAP and rScO2, generating the variable cerebral oximetry index (COx). When MAP is in the autoregulated range, COx approaches zero because there is no correlation between cerebral blood flow and arterial blood pressure. In contrast, when MAP is below the limit of autoregulation, COx is higher because there is a direct relationship between lower arterial blood pressure and lower cerebral blood flow. Thus, diminished autoregulation would be manifest as higher COx. Psychometric testing was performed before surgery and then 7 to 10 days and 4 to 6 weeks after surgery. A composite cognitive outcome was determined as the Z-score. Serum S100β, neuron-specific enolase, and glial fibrillary acidic protein were measured at baseline, after surgery, and on postoperative day 1. RESULTS: After adjusting for age and history of hypertension, COx ( P = 0.035) was higher and rScO2 lower ( P < 0.0001) in the BCP group than in the LDP group. After adjusting for baseline composite cognitive outcome, there was no difference in Z-score 7 to 10 days ( P = 0.530) or 4 to 6 weeks ( P = 0.202) after surgery between the BCP and the LDP groups. There was no difference in serum biomarker levels between the 2 position groups CONCLUSIONS: Compared with patients in the LDP, patients undergoing shoulder surgery in the BCP are more likely to have higher COx indicating diminished cerebral autoregulation and lower rScO2 . There were no differences in the composite cognitive outcome between the BCP and the LDP groups after surgery after accounting for baseline Z-score. Abstract : Published ahead of print September 26, 2014.